Collapsing glomerulopathy secondary to SARS-CoV-2 infection - Caballero-Linares, Max (2022)
A 36-year-old male with a history of moderate SARS-CoV-2 pneumonia three months earlier presented nephrotic syndrome with compromised renal function, where the histopathological diagnosis was compatible with collapsing glomerulopathy and, in electron microscopy of renal tissue, tested positive for the antibody against the nucleocapsid of SARS-COV-2 MA5-35943. Refractory to treatment with prednisone, remission of proteinuria was achieved when treated with tacrolimus. It is emphasized that SARS-CoV-2 infection can generate renal involvement by different pathological mechanisms.